2021
DOI: 10.1039/d1mh00244a
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic local stiffening in a supramolecular hydrogel network expedites stem cell mechanosensing in 3D and bone regeneration

Abstract: A cell-adaptable hydrogel containing microscopically local stiffening structures shows a heterogeneous and hierarchical hydrogel network topology, thereby facilitating the 3D stellate spreading of stem cells and promoting the bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…In contrast, hMSCs without osteogenic medium showed significantly low levels of ALP and RUNX2 on MeHA hydrogel, indicating that undifferentiated hMSCs expressed very low basal expression levels of these two markers (Figure S6). These results are consistent with the previous findings that the activation of the mechanotransduction pathway (YAP) is positively associated with the osteogenic differentiation of stem cells [31,32]. More importantly, our findings illustrate that the implementation of the nanostructure re-arranges the spatial distribution of cell-adhesive peptides to reinforce stem cell adhesion and differentiation on soft matrix.…”
Section: Local Rgd Clustering Supports Stem Cell Osteogenic Differentiation On Soft Matrixsupporting
confidence: 93%
“…In contrast, hMSCs without osteogenic medium showed significantly low levels of ALP and RUNX2 on MeHA hydrogel, indicating that undifferentiated hMSCs expressed very low basal expression levels of these two markers (Figure S6). These results are consistent with the previous findings that the activation of the mechanotransduction pathway (YAP) is positively associated with the osteogenic differentiation of stem cells [31,32]. More importantly, our findings illustrate that the implementation of the nanostructure re-arranges the spatial distribution of cell-adhesive peptides to reinforce stem cell adhesion and differentiation on soft matrix.…”
Section: Local Rgd Clustering Supports Stem Cell Osteogenic Differentiation On Soft Matrixsupporting
confidence: 93%
“…137 A following work from the same group also demonstrated that the mechanosensing and subsequent osteogenic differentiation of encapsulated MSCs could be further enhanced by chemical incorporation of acryloyl nanoparticles into the dynamic hydrogels, which created regionally stiff network structures. 398 Similarity, Wei et al described the assembly of a two-component host−guest hydrogel with Ada-grafted HA and in situ photopolymerized acryloyl-β-CD. These hydrogels exhibited reinforced mechanical properties, retained the desirable dynamic features, enabled chondrogenesis of the encapsulated human MSCs with greater collagen deposition, and promoted in vivo cartilage regeneration compared to covalently cross-linked MeHA hydrogels (Figure 24a).…”
Section: Stem Cells and Regenerative Medicinementioning
confidence: 99%
“…Yuan and colleagues reported a dynamic supramolecular hydrogel realizing the stiffening of a regional network with the addition of bioinert silica nanoparticles. 237 The silica nanoparticles were modified with methacryloyl groups (AcNPs) to photocrosslink with acryloyl β-cyclodextrin (Ac-β-CD) in gelatin host–guest hydrogels (GHG hydrogels) realizing the regional stiffen of hydrogel network. 237 Recently, microfluidic technology has been a conventional method for fabricating hydrogels with heterogeneous mechanical properties.…”
Section: The Development and Potential Applications Of 3d Msc Culture...mentioning
confidence: 99%
“…237 The silica nanoparticles were modified with methacryloyl groups (AcNPs) to photocrosslink with acryloyl β-cyclodextrin (Ac-β-CD) in gelatin host–guest hydrogels (GHG hydrogels) realizing the regional stiffen of hydrogel network. 237 Recently, microfluidic technology has been a conventional method for fabricating hydrogels with heterogeneous mechanical properties. The degradation of hydrogels will change the mechanical properties of hydrogels which have been made use of by the designers to manufacture dynamic 3D MSC culture systems.…”
Section: The Development and Potential Applications Of 3d Msc Culture...mentioning
confidence: 99%